Improvement of Upland Cotton Fiber Quality through Mutation of TAM 94L‐25. Issue 2 (1st March 2013) - Brown, Nino; Smith, C. Wayne; Auld, Dick; Hequet, Eric F.
ABSTRACT: The United States produces approximately 18 million 218‐kg bales of cotton ( Gossypium spp.) annually. The global market places value on longer fibers, mandating that breeders develop cultivars to meet this demand. Mutation has not been used extensively in upland cotton breeding for improving fiber quality traits. The objective of this study was to determine if treating cotton seeds of a genotype that produces longer fibers than most U.S. upland cotton cultivars with ethyl methanesulfonate (EMS) could result in mutant lines with exceptional fiber quality. TAM 94L‐25 (94L‐25) (Smith, 2003) (PI 631440) seeds were treated in 2001 with EMS at three times the least dosage to kill 50% of the seeds (LD50 ). Thirty mutation (M) lines of 94L‐25, derived as M3:4 progeny rows, 94L‐25 M0, and two check cultivars, FM 832 (Constable et al., 2001) (Plant Variety Protection [PVP] 9800258 or PI 603955) and PSC 355 (PI 612974), were grown in a randomized complete block design with four replications at College Station, TX (CS), and Weslaco, TX (W), in 2008 and 2009. High volume instrument (HVI) fiber properties were determined from hand harvested boll samples. Four M lines exceeded the lint yield of the M0 parent during both years. Fourteen M lines produced longer fibers than the M0 parent and both commercial checks while several M lines exhibited improved strength in 2008 but not in 2009. Treatment of 94L‐25 with the chemical mutagenic agent EMS was successful in producing selectable variation for yield and fiber traits simultaneously.